EPR analysis of extra‐ and intracellular nitric oxide in liver biopsies. Issue 6 (1st July 2016) - Dumitrescu, Sergiu D.; Meszaros, Andras T.; Puchner, Stefan; Weidinger, Adelheid; Boros, Mihaly; Redl, Heinz; Kozlov, Andrey V.
Abstract : Purpose: To develop an assay that can enable the quantification of intra‐ and extracellular nitric oxide (NO) levels in liver biopsies without application of potentially harmful exogenous NO traps. Theory: Electron paramagnetic resonance (EPR) spectroscopy is currently the most appropriate method of measuring NO in biological samples due to the outstanding specificity resulting from the interaction of NO with exogenous NO traps. Because such traps are not allowed in clinical settings, we tested the reliability of endogenous NO traps for the determination of NO levels in blood and liver compartments. Methods: Rats were injected with 0–8 mg/kg lipopolysaccharide (LPS) to gradually induce a systemic inflammatory response. Specific features of NO‐hemoglobin and NO–Fe EPR signals were quantified using a specifically developed calibration procedure. Results: Whereas both NO–hemoglobin (NO–Hb LIVER BLOOD ) and NO–Fe (NO–Fe LIVER ) complexes were detected in nonperfused liver tissue, only NO–Fe complexes were detected in perfused tissue and only NO–Hb complexes were detected in blood (NO–Hb BLOOD ). The NO concentrations increased in the sequence NO–Hb BLOOD  < NO–Fe LIVER  < NO–Hb LIVER BLOOD (9.4, 18.5, 27.9 nmol/cm 3, respectively at 2.5 mg/kg LPS). The detection limit of the method was 0.61 nmol/cm 3 for NO–Hb and 0.52 nmol/cm 3 for NO–Fe. Conclusion: The assay reported here does not influence natural NO pathways and enables the quantification of NO distribution in two liver compartments using a single liver biopsy. Magn Reson Med 77:2372–2380, 2017. © 2016 International Society for Magnetic Resonance in Medicine